New Rich: Upward Vertical Mobility of Illegal Cigarette Sellers in Pamekasan Regency - Hasanah, Iswatun; Wahyuningrum, Sri Rizqi; Aisa, Anna (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study aims to understand the unique social climbing phenomenon among illegal cigarette sellers along with its various dynamics, as well as to describe the resulting social and economic phenomena. The urgency of this research stems from the increasing circulation of illegal cigarettes and the resulting shifts in social structures within rural communities, which have not been sufficiently explored in previous studies. The method used is field research with a qualitative descriptive case study approach, employing data collection techniques such as non-participant observation and comprehensive interviews. The research was conducted in two villages in Pamekasan Regency, with three illegal cigarette sellers as research subjects. Data analysis follows the Miles and Huberman model. The results of the study show: (1) A lack of social sanctions from the community regarding the circulation of illegal cigarettes; (2) Social climbing behavior arises because individuals highly value social status and perceive social appreciation as closely tied to symbols of wealth; (3) Social climbing is related to the individual's self-concept and their ability to accept their life circumstances. Strengthening gratitude attitudes is essential so that the pursuit of livelihood considers not only financial gain but also psychological well-being and lawful behavior. The findings of this research are expected to contribute to the understanding of deviant economic practices and their social impacts, providing insights for policymakers in formulating more effective social and legal interventions to reduce illegal trade activities.